Domain of influence theorem in the theory of bending of micropolar elastic plates with stretch - Ciarletta, M.; Passarella, F. (Archives of Mechanics, 1999)
In the context of linear theory of bending of micropolar plates with stretch, a domain of dependence inequality associated with the initial-boundary value problem is derived and a domain of influence theorem is established. It is shown that for a finite time, a solution corresponding to the data of a bounded support vanishes outside a bounded domain.